Mechanism of enhanced nitrate reduction via micro-electrolysis at the powdered zero-valent iron/activated carbon interface - Luo, Jinghuan; Song, Guangyu; Liu, Jianyong; Qian, Guangren; Xu, Zhi Ping (Journal of colloid and interface science, 2014)
[Display omitted] •Fe0/AC micro-electrolysis was first introduced for nitrate reduction.•Fe0/AC performed much better nitrate reduction than Fe0 only.•Fe0/AC achieved 73% of nitrate reduction efficiency even at pH 6.•Mechanism study showed AC played an important role in electron transfer. Nitrate reduction by zero-valent iron (Fe0) powder always works well only at controlled pH lower than 4 due to the formation of iron (hydr)oxides on its surface. Fe0 powder combined with activated carbon (AC), i.e., Fe0/AC micro-electrolysis system, was first introduced to enhance nitrate reduction in aqueous solution. Comparative study was carried out to investigate nitrate reduction by Fe0/AC system and Fe0 under near-neutral conditions, showing that the Fe0/AC system successfully reduced nitrate even at initial pH 6 with the reduction efficiency of up to 73%, whereas for Fe0 only ∼10%. The effect of Fe0 to AC mass ratio on nitrate reduction efficiency was examined. Easier nitrate reduction was achieved with more contact between Fe0 and AC as the result of decreasing Fe0 to AC mass ratio. Ferrous ion and oxidation–reduction potential were measured to understand the mechanism of enhanced nitrate reduction by Fe0/AC micro-electrolysis. The results suggest that a relative potential difference drives much more electrons from Fe0 to AC, thus generating adsorbed atomic hydrogen which makes it possible for nitrate to be reduced at near-neural pH. Fe0/AC micro-electrolysis thus presents a great potential for practical application in nitrate wastewater treatment without excessive pH adjustment.